Recent consideration on diagnosis and therapy of gingival desquamative lesions: Case report - Ljušković Bešir; Daković Dragana (Serbian Medical Society - Dental Section, Belgrade, 2003)
The purpose of the studywas to present a case of desquamative gingivitis and indicate to diagnosis and therapy od desquamative lesions of gingivae. The case of desquamative gingivitis in 75 year old patient is shown. Despite pathohistological and immunofluorescent analyses having been done, the origin of the disease could not have been established at first. The undertaken therapy gave limited results. The patient did not show up for the check up for 2,5 years. When he finally came, the clinical situation was the same as the first examination. The bioptic material gave positive results. Continuous linear deposits of IgG and IgA along the basement membrane were found. The histopathological diagnosis presentes a pemphigoid. Metilprednisolon 40mg per day was prescribed, with gradual dicrease of the dose, along with tetracycline 4x250mg per day. Therapy lasted for six and a half months. Changes on the gingivae completely retreated after three months.